The relationship between junk food consumption and other factors with the incidence of dysmenorrhea in adolescent girls - Ardelia Evani; Sugiatmi Sugiatmi (AcTion: Aceh Nutrition Journal, 2024)
Dysmenorrhea has an impact on the disruption of daily activities and a decrease in physical conditions such as fatigue and lethargy, decreased appetite, and decreased sleep quality. More than 50% of women worldwide experience dysmenorrhea. The prevalence of dysmenorrhea in Indonesia is 64,25%. This study aimed to determine factors associated with the incidence of dysmenorrhea in adolescent girls. The study used a cross-sectional design and was conducted from May to June 2023. Using a random sampling technique, the sample consisted of 63 students at State Senior High School 11, South Tangerang. Data were collected by completing questionnaires on dysmenorrhea, junk food consumption, and sleep quality. Interviews were conducted for calcium intake data using a 2 x 24-hour food recall and measuring height and weight. Data analysis using chi-square tests. Results: There was a relationship between junk food consumption (p=0,022), sleep quality (p=0,035), calcium intake (p=0,030) and the incidence of dysmenorrhea. Meanwhile, there was no significant relationship between percent body fat (p=1,000), nutritional status (p=0,638) and the incidence of dysmenorrhea. In conclusion, junk food consumption, sleep quality, and calcium intake were associated with the incidence of dysmenorrhea. In contrast, body fat percentage and nutritional status were not associated with the incidence of dysmenorrhea in adolescent girls.